Letter (copy) : Spanish Relief Fund - Tewson, Vincent
029-0128-001 HVT/MS/1068 Secretary's 12th June, 1937. Mr. F. Morrice, 19, Godfrey Road, Newport, Mon. Dear Mr. Morrice, Spanish Relief Fund. I have had some correspondence with Mr. Cecil J. Beer who is Viceconsul for Spain at Newport, in regard to the possibility of our placing food stuffs on board the "Sil" for despatch to Northern Spain. I do not know whether you actually have any food stuffs. If so they could be sent on this ship. If, however, you are as I hope concentrating on the raising of funds then the money could go to our fund as we are hoping to send a fairly large consignement. Whether we can do this on the "Sil" is still in doubt as we are desirous that the food should go to Gijon. We are in touch with the agents on this matter and have not yet got definite information. We should be glad to increase our consignment by the amount of any contribution which you may earmark for this purpose. But if you have actually collected food stuffs there is no objection to your sending it by the "Sil" even if it were to go to Santander and not Gijon. Yours sincerely, Assistant Secretary. 292/946/29/128